(3QSGdI aj bjGe GdCQVs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg MeOkG HZjQ fgGjJg hHYO aEf GdTjN CeQfi Cf CTQM Edi ePgH GdMb ai YdI bjGe GdGQV ai NHQg GdPi ehajg HeG jbQH JUhQg s
(3BNQgG (B:s
(3hbGd HYVge Cf CLRGA GdGQV EfeG Edi GdGQV ZTbkG dcdJjgeG hbGd HYVge jJMQc fOGJgG Hd jLPH GdNdGA agPG eG MVQfG ai gPg GdSGYI ef CQGA GdbOeGA ai GdGQV hdfNJe GdQSGdI hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(423(6)) s
Keywords: (3GdadSaI hGdefWbs